A forma do pecado: adaptação cinematográfica dos quadrinhos de Sin City - Danilo Aroeira de Pinho Tavares (2014)
Although adaptations characterize a number of changes during the process of translation from one medium to another, several of them can be considered as formal choices. By analyzing the 2005 motion picture Sin City, directed by Robert Rodriguez, adapted from the eponymousgraphic novel by Frank Miller published in the early nineties, I compare the two works and go through the formal aspects that differ from one another storyline, script, visual, framing and sound to better understand the choices made. The concepts of adaptation and intermediality by Madalena Punzi (2007), Ilmeda Welehan (1999) and Adalbert Müller (2013) were used. Studies by Brian McFarlane (1996) also helped in the choice of methodological procedures adopted for the analysis. The comparison between the two versions is then done withoutrestricting an attempt to map the possible (in)fidelities during the transposition process. Instead, I seek to identify the ways in which the narratives are related, as well as the part played in the production of meaning for the viewer and how the specificities of each medium film and comics have determined the final result.